INTRODUCTION OF ARTIFICIAL INTELLIGENCE IN MEDICAL EXAMINATIONS USING ACOUSTICS (Western European Journal of Medicine and Medical Science, 2025)
Acoustic technologies are widely used in medical practice, ranging from diagnostic procedures to therapeutic treatment methods. This article discusses the main areas of use of acoustics in medicine, including ultrasound diagnostics, therapeutic methods and the latest developments in acoustic biomedicine. Special attention is given to the prospects of highintensity ultrasound and its combination with other therapeutic methods.